1994
DOI: 10.1164/ajrccm.149.2.8306039
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension and hypoxemia in obstructive sleep apnea syndrome.

Abstract: To determine whether pulmonary hypertension (PH) can occur in obstructive sleep apnea syndrome (OSAS) in the absence of lung or primary cardiac disease, we studied 27 patients (26 males, mean age 49 +/- 10 yr) with OSAS (respiratory disturbance index [RDI] > 10 events/h) in whom clinically significant lung or cardiac diseases were excluded. Pulsed Doppler measurements of pulmonary hemodynamics, pulmonary function tests, arterial blood gas analysis, and polysomnography were performed. A total of 11 OSAS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
117
1
9

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(132 citation statements)
references
References 21 publications
5
117
1
9
Order By: Relevance
“…Nonetheless, it is known that patients with OSAS can have low values of Pa,O 2 related to the development of pulmonary hypertension. The development of pulmonary hypertension cannot be predicted by OSAS severity, FEV1 values, BMI or smoking habit [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is known that patients with OSAS can have low values of Pa,O 2 related to the development of pulmonary hypertension. The development of pulmonary hypertension cannot be predicted by OSAS severity, FEV1 values, BMI or smoking habit [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors found pulmonary hypertension also in patients with pure OSAS or those patients who are not extremely obese [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with cardiovascular disease, such as hypertension [2,3] pulmonary hypertension [4,5], myocardial infarction [6], or stroke [7]. Furthermore, patients with OSAS suffer from decreased daytime performance [8].…”
mentioning
confidence: 99%